Phylogenetic and In Silico Functional Analyses of Thermostable-Direct Hemolysin and tdh-Related Encoding Genes in Vibrio parahaemolyticus and Other Gram-Negative Bacteria - Bhowmik, Sushanta K. (Hindawi Publishing Corporation, 2014)
Emergence and spread of pandemic strains of Vibrio parahaemolyticus have drawn attention to make detailed study on their genomes. The pathogenicity of V. parahaemolyticus has been associated with thermostable-direct hemolysin (TDH) and/or TDH-related hemolysin (TRH). The present study evaluated characteristics of tdh and trh genes, considering the phylogenetic and in silico functional features of V. parahaemolyticus and other bacteria. Fifty-two tdh and trh genes submitted to the GenBank were analyzed for sequence similarity. The promoter sequences of these genes were also analyzed from transcription start point to −35 regions and correlated with amino acid substitution within the coding regions. The phylogenetic analysis revealed that tdh and trh are highly distinct and also differ within the V. parahaemolyticus strains that were isolated from different geographical regions. Promoter sequence analysis revealed nucleotide substitutions and deletions at −18 and −19 positions among the pandemic, prepandemic, and nonpandemic tdh sequences. Many amino acid substitutions were also found within the signal peptide and also in the matured protein region of several TDH proteins as compared to TDH-S protein of pandemic V. parahaemolyticus. Experimental evidences are needed to recognize the importance of substitutions and deletions in the tdh and trh genes.